ANALISIS EROSI DAN SOSIAL EKONOMI TERHADAP DEGRADASI LAHAN SUB DAS WAIBLAMA - Marianus Mayolis; I.N.Prijo Soetedjo; Philiphi de Rozari (AGRICA, 2026)
This study aims to determine the problems and impacts of land degradation on the geophysical, biological, and socio-economic environments in the Waiblama Sub-watershed. One of the main causes of land degradation is erosion. To determine erosion prediction and conservation planning in the Waiblama Sub-watershed area, Natar Mage Village and Tanarawa Village, Waiblama District, Sikka Regency, using the USLE method. The results of the study showed that the magnitude of erosion in the Waiblama Sub-watershed ranged from 0.05 to 1719.72 tons/ha/year, which is classified as very light to very heavy. The highest importance value index at the tree level is dominated by the Candlenut plant species (Aleurites moluccanus) with a relative density (KPR) of 0.11 to 0.26% and an importance value index (INP) of 6.74 to 10.96%. The pole level is dominated by the Lamtoro species (Leucacena leucocephala) with a KPR of 1.31 to 1.67% and an INP of 10.08 to 15.84%. The most dominant sapling level is the turi plant species (Sesbania grandifora) with a KPR of 0.53 to 1.82% and an INP of 6.07 to 14.70%. The most dominant seedling level is the gletang grass (Tridaxprocumbenns) with a relative density (KPR) of 6.67 to 29.26% and an importance value index (INP) of 18.70 to 63.34%.